Emerging pedagogies for the use of iPads in schools. (29th December 2015) - Geer, Ruth; White, Bruce; Zeegers, Yvonne; Au, Wing; Barnes, Alan
Abstract: iPads are becoming popular as 1:1 devices in many classrooms, enabling teachers to implement pedagogies that will enhance student learning. Such mobile tools offer many affordances which can increase student motivation and autonomy. Nevertheless, without a change in pedagogy, they are unlikely to bring about any significant impact on student learning. Using the SAMR model, this initial study of four schools explores the impact of iPads on pedagogy and the changes that were evident. Using multiple data collection techniques, the study has shown that there have been some changes in teachers' pedagogy that lead to increased collaboration, communication, student self‐reliance and the development of authentic experiences. However, more time and professional learning are needed to bring about a transformation in pedagogy across the school.